Insights into foraging behavior from multi-day sound recording tags on goose-beaked whales (Ziphius cavirostris) in the Southern California Bight - Coates, Shannon N.; Sweeney, David A.; Falcone, Erin A.; Watwood, Stephanie L.; Rone, Brenda K.; DeRuiter, Stacy L.; Barlow, Jay; Dolan, Karin A.; Morrissey, Ronald P.; DiMarzio, Nancy A.; Jarvis, Susan M.; Andrews, Russel D.; et al. (Frontiers in Marine Science, 2024)
In 2019 and 2020, six Sound and Motion Recording and Telemetry tags were deployed on Goose-beaked whales (Ziphius cavirostris) in Southern California, resulting in 401 hours of acoustic and diving data. Foraging dives were manually identified by the presence of echolocation pulses and buzzes, and generalized additive models were used to assess factors influencing foraging behavior. The median bathymetric depth at the site of foraging dives was 1,419 m (IQR = 359). Maximum dive depth was highly correlated with bathymetric depth around the dive location. Individuals started echolocating on descent into foraging dives at a median depth of 410 m (IQR = 74); pulses were not observed shallower than 292 m. Echolocation ceased while in the bottom phase for 81.6% of dives, at a median depth of 1,265 m (IQR = 472); pulses were not observed shallower than 587 m on ascent. The median depth of buzzes was 1,215 m (IQR = 479) with 63% occurring during the bottom phase. As dive depth increased, there was a corresponding increase in dive and echolocation durations, echolocation end depth, and bottom phase echolocation depth inter-quartile range. The median difference between dive depth and bottom phase median echolocation depth was 98.3 m (IQR = 48.5), suggesting Z. cavirostris in this region typically forage in a narrow band close to the seafloor. Individuals exhibited longer echolocation durations, produced more echolocation pulses, and both started and ended echolocating deeper in the San Nicolas Basin than in adjacent regions. These extended, high-resolution records of diving and foraging both validate and expand upon the findings of prior studies of Z. cavirostris in Southern California and provide insights into factors that influence their activity in a region where they are subject to high levels of anthropogenic disturbance.